Timber Volume Estimation Model for Merchantable Tree Species in Sarmi Regency, Papua - Kuswandi, Relawan Kuswandi (Forestry Department, University of Muhammadiyah Makassar, 2016)
Precise forest inventory to estimate standing stock is needed in forest management planning. Therefore, it is necessary to have proper and reliable tools in estimating merchantable timber volume. This research was intended to build an accurate model to estimate timber volume for merchantable species in logging concession of PT Wapoga Mutiara Timber, Sarmi Regency. Regression equation between diameter and length did not have a significant correlation (coefficient of determination, R2 = 6.7 %). The best equation to estimate table tree volume based on validation test in logging concession of PT Wapoga Mutiara Timber was Log V = - 3.34 + 2.16 log d.